Structural Characterization and Magnetic Behavior Due to the Cationic Substitution of Lanthanides on Ferrite Nanoparticles - Melo-Hurtado, F (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
A new series of [Fe3−xLnx]O4 nanoparticles, with Ln = Gd; Dy; Lu and x = 0.05; 0.1; 0.15, was synthesized using the coprecipitation method. Analyses by X-ray diffraction (XRD), Rietveld refinement, and high-resolution transmission electron microscopy (HRTEM) indicate that all phases crystallized in space group (Formula presented.), characteristic of spinels. The XRD patterns, HRTEM, scanning electron microscopy analysis (SEM-EDS), and Raman spectra showed single phases. Transmission electron microscopy (TEM), Rietveld analysis, and Scherrer’s calculations confirm that these materials are nanoparticles with sizes in the range of ~6 nm to ~13 nm. Magnetic measurements reveal that the saturation magnetization (Ms) of the as-prepared ferrites increases with lanthanide chemical substitution (x), while the coercivity (Hc) has low values. The Raman analysis confirms that the compounds are ferrites and the Ms behavior can be explained by the relationship between the areas of the signals. The magnetic measurements indicate superparamagnetic behavior. The blocking temperatures (TB) were estimated from ZFC-FC measurements, and the use of the Néel equation enabled the magnetic anisotropy to be estimated. © 2024 by the authors.